Impact of visual context on public perceptions of non-human primate performers. - Katherine A Leighty; Annie J Valuska; Alison P Grand; Tamara L Bettinger; Jill D Mellen; Stephen R Ross; Paul Boyle; Jacqueline J Ogden (PLoS ONE)
Prior research has shown that the use of apes, specifically chimpanzees, as performers in the media negatively impacts public attitudes of their conservation status and desirability as a pet, yet it is unclear whether these findings generalize to other non-human primates (specifically non-ape species). We evaluated the impact of viewing an image of a monkey or prosimian in an anthropomorphic or naturalistic setting, either in contact with or in the absence of a human. Viewing the primate in an anthropomorphic setting while in contact with a person significantly increased their desirability as a pet, which also correlated with increased likelihood of believing the animal was not endangered. The majority of viewers felt that the primates in all tested images were "nervous." When shown in contact with a human, viewers felt they were "sad" and "scared", while also being less "funny." Our findings highlight the potential broader implications of the use of non-human primate performers by the entertainment industry.